Organizational culture in higher education institutions: concepts, importance and relationship with social responsibility - Osorio-Galindo, Franklin M. (2023)
His review article arises from the academic meeting of the seminar organization and management of higher education institutions of the doctorate in Educational Sciences of the Metropolitan University of Education, Science and Technology (UMECIT). In its analysis, the conceptual positions of development and organizational culture are exposed from the field of higher education, relevance is made in the relationship with management systems, its importance with social responsibility and the conjugation of three aspects: science , technology, society and their relationship with the productive sector The information collected is given through bibliographic consultation and tracking in electronic journals and repositories. In this way, there is access to research, which provides important elements for the conceptual relationship. The analysis of the information is developed through a signing matrix, which facilitates the interpretation, relationship and theoretical understanding of the documents, within the findings a referential framework is established on the beliefs, values ​​and organizational perceptions of the agents that participate in the actions, and the elements that characterize and direct the culture of the institutions, that is, they enable the transformational capacity and adaptation to the needs of the environment.